Opacification of hydrophilic intraocular lenses associated with vitrectomy and injection of intraocular gas - Marcovich, Arie L.; Tandogan, Tamer; Bareket, Mor; Eting, Eva; Kaplan-Ashiri, Ifat; Bukelman, Amir; Auffarth, Gerd U.; Khoramnia, Ramin (BMJ open ophthalmology, 2018)
Objective To report 11 cases of intraocular lens (IOL) opacification after pars plana vitrectomy (PPV) involving intravitreal gas injection. - Methods and analysis Eleven cases of hydrophilic IOLs that opacified following PPV with intravitreal gas injection are described. Eight IOLs were explanted and analysed by light microscopy and scanning electron microscopy. Staining with alizarin red and von Kossa stains, as well as energy dispersive X-ray spectroscopy (EDX) were performed. Three IOLs were not explanted. The surgeons attached the clinical data. - Results The IOLs were hydrophilic acrylic produced by six manufacturers. Six patients underwent primarily phacoemulsification with IOL implantation. PPV with intravitreal gas injection was performed 3 months-6 years afterwards. The other five patients underwent combined phacoemulsification with IOL implantation and PPV with intravitreal gas injection. IOL opacification was recorded 1 month -6 years after PPV. In eight patients, the IOLs were explanted 1 month-9 years after opacification was noticed. In three patients, the opacified IOL was not explanted. IOLs had opacified mainly anteriorly at the pupillary entrance or capsulorhexis opening. Light microscopy demonstrated granular surface deposits on the IOLs that stained positive for calcium by alizarin red and von Kossa stains. EDX analysis of the deposits detected calcium and phosphorus. - Conclusions Hydrophilic acrylic IOLs can opacify due to calcium deposition after PPV and intravitreal gas injection and may require IOL explantation. A hydrophobic IOL may be preferred when a simultaneous phacoemulsification and vitrectomy with intravitreal gas is performed.
Gesehen am 18.10.2019